Classification of postoperative complications in plastic and reconstructive surgery: a systematic review - Shaani Singhal; Vicky Tobin; David J Hunter-Smith; Warren M Rozen (Australasian Journal of Plastic Surgery, 2024)
**Introduction:** Postoperative complications are an integral aspect of the surgical audit, being a surrogate marker of surgical quality. Despite demonstrated efficacy in most specialties, there is scarce validation of current systems in plastic and reconstructive surgery, let alone a system unique to the specialty. This review aims to establish the efficacy of current systems in plastic and reconstructive surgery and formulate a classification unique to our specialty. **Methods:** A PubMed literature search was performed in January 2023 encompassing all available literature. Search terms included ‘classification’, ‘grading’, ‘postoperative complications’ and ‘adverse events’. Further additions through bibliographic linkage generated a total of 363 articles. **Results:** Twenty-four papers were related to plastic and reconstructive surgery. Sixteen used current systems to describe postoperative complications, whereas eight papers used a system designed uniquely for plastic and reconstructive surgery. The downfall of conventional systems is the simplicity of return to the operating theatre, constituting a single grade in the Clavien-Dindo Classification. Return to theatre has a broad scope for heterogeneity in plastic and reconstructive surgery, particularly in reconstructive patients. A modification of the Clavien-Dindo Classification is proposed. **Conclusion:** There is limited efficacy of current classification systems for postoperative complications in plastic and reconstructive surgery nor a well-validated system unique to the specialty. A modified system with a detailed emphasis on return to the theatre will be of value to plastic and reconstructive surgery and ideally correlate with important outcomes. This will be validated in a retrospective review of the complication audit from the developing institution.